Status of meat alternatives and their potential role in the future meat market — A review - Lee, Hyun Jung (Asian-Australas J Anim Sci, 2020)
Plant-based meat analogues, edible insects, and cultured meat are promising major meat alternatives that can be used as protein sources in the future. It is also believed that the importance of meat alternatives will continue to increase because of concerns on limited sustainability of the traditional meat production system. The meat alternatives are expected to have different roles based on their different benefits and limitations. Plant-based meat analogues and edible insects can replace traditional meat as a good protein source from the perspective of nutritional value. Furthermore, plant-based meat can be made available to a wide range of consumers (e.g., as vegetarian or halal food products). However, despite ongoing technical developments, their palatability, including appearance, flavor, and texture, is still different from the consumers’ standard established from livestock-based traditional meat. Meanwhile, cultured meat is the only method to produce actual animal muscle-based meat; therefore, the final product is more meat-like compared to other meat analogues. However, technical difficulties, especially in mass production and cost, remain before it can be commercialized. Nevertheless, these meat alternatives can be a part of our future protein sources while maintaining a complementary relationship with traditional meat.